Significant linkage disequilibrium between the Huntington's disease locus and markers at loci D4S10, D4S95, and D4S111 in Northern Ireland. Issue 12 (December 1993) - Morrison, P J; Graham, C A; Nevin, N C
Abstract : An analysis of the Northern Ireland Huntington's disease (HD) population of 75 families showed significant linkage disequilibrium between the HD gene and DNA markers at D4S95, D4S10, and D4S111. As the linkage disequilibrium at loci D4S10 and D4S111 is different from previous studies in the UK, but similar at locus D4S95, this suggests either that the HD mutation(s) in the Northern Ireland and British populations is not of common origin or that the haplotype of the common HD mutation has changed over time subsequent to divergence from a common origin.